STUDY OF ANTI-INFLAMMATORY ACTIVITY OF “ORTOF-S” TABLETS - Saidhabibovna, Yunusova Malikakhon; Jurabayevna, Allayeva Munira; Mannanovna, Yunusova Kholida; qizi, Jaloliddinova Muattar Shukhrat; qizi, Anvarova Farangiz Jamshid (International Journal of Membrane Science and Technology, 2023)
The results of the study of pharmacological studies of the recommended tablets “Ortof-S” by the method “carrageenan paw edema in rats” are presented. The first stage of the study, the anti-inflammatory effect of the compared drugs “Ortof-S”, manufactured by LLC “SAMO”, Uzbekistan and “Ketaneym”, manufactured by “NEOUNIVERSE LLP”, London, UK, was studied by the method of “carrageenan paw edema in rats” anti-inflammatory activity bioavailability is to determine the solubility or release time of the drug from the medicinal forms. It was found that the solubility test characterizes the biological availability of the drug in the first approximation, since in practice there is a very frequent correlation between the rate of dissolution and absorption. The solubility, foreign impurities and the quantitative content of active substances were studied.